Kekerasan di Tempat Kerja dalam Pelayanan Kesehatan - Hairunisa, Nany (Fakultas Kedokteran Universitas Trisakti, 2023)
Violence in the workplace is an act or threat of violence against workers, both inside and outside the workplace, ranging from insults, threats, intimidation, and physical assault to murder. Although violence in the workplace has become a global concern, the true extent of this problem is still underreported due to low awareness and lack of awareness of the issues within the body. Therefore, if violence in the workplace is not addressed, especially in the health sector, it will become a global phenomenon that will disrupt the peace and stability of the working community and pose a risk to the health and welfare of society. Therefore, this review aims to identify the risk factors and impacts of workplace violence in health care and demonstrate the collaborative efforts needed to support managing and preventing violence in the workplace. Keywords: Violence, workplace, Healthcare worker.